Fundamental characterization of cryogenic machining by applying solid lubricants - Sterle, Luka (visokošolska dela, 2022)
Cryogenic machining based on liquid carbon dioxide (LCO2) represents a sustainable and clean way of manufacturing and enables the substitution of conventional metalworking fluids such as water-based emulsions. In machining processes, LCO2 is a cooling medium to which various lubricants are added to improve lubrication properties. Solid lubricants can reduce friction even in the most demanding conditions. The concept of implementing solid lubricants in LCO2 to achieve cooling and lubricating properties is thus a novelty in the field of cryogenic machining. Within the scope of the doctoral thesis, a single-channel system for the supply of oil- and solid-lubricated LCO2 was developed. The system implementation for feeding the mixture through the spindle and the tool directly into the machining process was carried out. A special tribometer was used to analyse the lubrication properties of different cooling/lubrication strategies, including pure LCO2 and oil- and solid-lubricated LCO2. Milling and drilling processes were used to determine the basic properties of cryogenic machining based on tool life, integrity of the machined surface, cutting forces and cutting temperature. Predictive models were developed to optimise cryogenic machining for sustainable manufacturing by reducing the consumption of coolants and lubricants. Analysis of the machined surfaces with an electron beam microscope proved the benefit of using solid lubricants in terms of the integrity of the machined surface and the final cleanliness of the part.
Keywords: cryogenic machining; cutting temperature; Disertacije; dissertations; integriteta površine; kriogeno odrezovanje; Odrezovanje; rezalna temperatura; solid lubricants; surface integrity; trdna maziva; tribologija; tribology; tribometer